Analysis of the economic viability of a photovoltaic generation project applied to the Brazilian housing program "Minha Casa Minha Vida". (September 2017) - Vale, A.M.; Felix, D.G.; Fortes, M.Z.; Borba, B.S.M.C.; Dias, B.H.; Santelli, B.S.
Abstract: In Brazil, distributed grid-connected solar photovoltaic (PV) plays an increasingly role due to advances in PV technology, combined with decreasing capital costs and subsidies. Therefore, this paper aims conduct an economic analysis of two projects in "Minha Casa Minha Vida" (MCMV) governmental program, one in the state São Paulo and the other in the state of Piauí, using distributed photovoltaic power generation. The MCMV is the Brazilian government's housing program that gives access to home ownership to low-income Brazilians in urban and rural areas. Such analysis was undertaken by the evaluation of the net present value (NPV) and internal rate of return (IRR), considering a Minimum Attractive Rate of Return (MARR) and by varying the annual growth of energy tariffs over 25 years of operation, which represents the expected lifespan of solar panels. These two cities were chosen because their federal states have different actions with respect to tax matters. Such difference, in particular, will be examined and explored in this article. Results show that even though Piauí presents a higher average solar radiation than São Paulo, the impact of ICMS exemption guarantees an advantage of investing in São Paulo. Highlights: Photovoltaic Systems applied in popular houses. DG applied in Social Projects. Economic Analysis in Photovoltaic Systems. Brazilian government´s housing program – cases analysis.